Determinación del efecto de las enzimas amilasa, proteasa y xilanasa sobre el rendimiento productivo de pollos de engorde en las fases de desarrollo y acabado en la ciudad de Babahoyo. - Moreno Coronel, Eloy Antonio (2011)
The present research was developed in the poultry complex “San Pablo” experimental farm, at “Facultad de Ciencias Agropecuarias de la Universidad Técnica de Babahoyo “, located at the 7,5th km of the highway Babahoyo – Montalvo, in the province of Los Rios, Republic of Ecuador. With 42 days of research, were used a total of 200 broiler chickens of the Ross genetic line, distributed in two experimental fields of 100 units each one (T0) and (T1), used as witness treatment field and experimental treatment field respectively.